Dietary salt blunts vasodilation by stimulating epithelial sodium channels in endothelial cells from salt‐sensitive Dahl rats. (10th May 2017) - Wang, Zi‐Rui; Liu, Hui‐Bin; Sun, Ying‐Ying; Hu, Qing‐Qing; Li, Yu‐Xia; Zheng, Wei‐Wan; Yu, Chang‐Jiang; Li, Xin‐Yuan; Wu, Ming‐Ming; Song, Bin‐Lin; Mu, Jian‐Jun; Yuan, Zu‐Yi; et al.
Abstract : Background and Purpose: Our recent studies show that the reduced activity of epithelial sodium channels (ENaC) in endothelial cells accounts for the adaptation of vasculature to salt in Sprague–Dawley rats. The present study examines a hypothesis that enhanced ENaC activity mediates the loss of vasorelaxation in Dahl salt‐sensitive (SS) rats. Experimental Approach: We used the cell‐attached patch‐clamp technique to record ENaC activity in split‐open mesenteric arteries. Western blot and immunofluorescence staining were used to evaluate the levels of aldosterone, ENaC, eNOS and NO. Blood pressure was measured with the tail‐cuff method and the artery relaxation was measured with the wire myograph assay. Key Results: High‐salt (HS) diet significantly increased plasma aldosterone and ENaC activity in the endothelial cells of Dahl SS rats. The endothelium‐dependent artery relaxation was blunted by HS challenge in these rats. Amiloride, a potent blocker of ENaC, increased both phosphorylated eNOS and NO and therefore prevented the HS‐induced loss of vasorelaxation. As, in SS rats, endogenous aldosterone was already elevated by HS challenge, exogenous aldosterone did not further elevate ENaC activity in the rats fed with HS. Eplerenone, a mineralocorticoid receptor antagonist, attenuated the effects of HS on both ENaC activity and artery relaxation. Conclusions and Implications: These data suggest that HS diet blunts artery relaxation and causes hypertension via a pathway associated with aldosterone‐dependent activation of ENaC in endothelial cells. This pathway provides one of the mechanisms by which HS causes hypertension in Dahl SS rats. Linked Articles: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc